Potential Spread of Desert Locust Schistocerca gregagia (Orthoptera: Acrididae) under Climate Change Scenarios - Qianhong Tang; Jianmeng Feng; Donglin Zong; Jing Zhou; Xiaokang Hu; Bingru Wang; Tao Wang (Diversity, 2023)
The desert locust Schistocerca gregagia (Forskål, 1775) is one of the most harmful migratory pests in the world, posing a major threat to agricultural production, livelihoods, and food security. Climate, land use, and topography influence the distribution of desert locusts, but few studies have integrated all the factors on a global scale to explore the suitable areas for desert locusts and the paths through which this species could potentially spread. In this study, we established ensemble distribution models to investigate the distribution patterns and driving factors of desert locusts under baseline and future scenarios; we used ensembled niche dynamic models to evaluate their niche conservation during outbreaks. The results showed that the most important factor influencing desert locust distribution is climate, especially the minimum temperature of the coldest month, the annual precipitation, and the mean temperature of the driest quarter. Some areas with little or no desert locust distribution at present will be suitable for desert locusts in the future, and highly suitable contiguous areas may become the dispersal paths. The results also showed that the climatic niche of the desert locust is still conservative, which might explain why desert locusts tend to retreat after intermittent outbreaks rather than settle at the site of invasion. Therefore, more attention should be paid to the areas that are highly suitable for desert locusts, the key factors driving their outbreaks, and the shifting of their climatic niche in order to prevent desert locusts from settling in invasion areas and affecting local ecosystems and food security.